PATTERNS FOR THE IMPLEMENTATION OF CONFIDENTIAL SUPERVISION AND GUIDANCE DURING THE ASIMILATION PROGRAM AT HOME - Faisal Abdurrachman Harits (Polteknik Ilmu Pemasyarakatan, 2020)
In writing this paper the author discusses the Implementation Pattern of Supervision and Guiding Prisoners During the Assimilation Program at Home. It is motivated that the Parole Officer also has an important role in providing supervision and guidance to correctional clients who get assimilation programs at home. To carry out their duties and functions as supervisors and mentors, it is not uncommon for Parole Officer to experience a variety of external and internal obstacles. The purpose of the research conducted is to describe and analyze how the pattern of guidance and supervision carried out by the Parole Officer.In writing this paper the method of approach used is sociological juridical means a study conducted on the real state of society or the environment of the community with the intent and purpose of finding facts which then leads to identification and ultimately to the resolution of problems. Then the data obtained were analyzed in a descriptive quantitative manner, namely the problem solving procedure by describing the data that had been obtained. The results of research conducted that the way of guidance carried out by the Parole Officer is the interview method using the Whastsapp video call to minimize face-to-face activities. Whereas the guidance provided by Parole Officer Bapas Kelas II Pati is to use the individual guidance and group guidance methods In carrying out the guidance program, there are several factors from clients that are the cause of repeating the criminal acts again, namely economic factors and narcotics dependency factors. Efforts are being made to overcome this problem, namely: by immediately revoking the assimilation program at home and put it into a straft cell according to Permenkumham No. 10 of 2020.